Enzymatic Dissolution of Biocomposite Solids Consisting of Phosphopeptides to Form Supramolecular Hydrogels - Shi, Junfeng (Chemistry, 2015)
Enzyme-catalyzed dephosphorylation is essential for biomineralization and bone metabolism. Here we report the exploration of using enzymatic reaction to transform biocomposites of phosphopeptides and calcium (or strontium) ions to supramolecular hydrogels as a mimic of enzymatic dissolution of biominerals. (31)P NMR shows that strong affinity between the phosphopeptides and alkaline metal ions (e.g., Ca(2+) or Sr(2+)) induces the formation of biocomposites as precipitates. Electron microscopy reveals that the enzymatic reaction regulates the morphological transition from particles to nanofibers. Rheology confirms the formation of a rigid hydrogel. As the first example of enzyme-instructed dissolution of a solid to form supramolecular nanofibers/hydrogels, this work provides an approach to generate soft materials with desired properties, expands the application of supramolecular hydrogelators, and offers insights to control the demineralization of calcified soft tissues.